Profiling and algorithms used for automated decision-making: the Influence of GDPR - Tihomirova, Ksenija (Riga Graduate School of Law, 2021)
The current study, in the form of a systematic literature review, considers the specific implications of using algorithmic calculations to make assumptions based on patterns in big data and the related decision-making process. The question is how algorithmic decision-making meaningfully differs from other forms of big data analysis and use, and what implications does that have for both business ethics and related privacy laws. Specifically, in the European Union, the measure of legality is according to the General Data Protection Regulation (GDPR), which is designed to protect the privacy of all EU citizens. However, there is a concern that the law is insufficient to protect against the more invasive nature of algorithmic configurations and to protect individual from the application of incorrect assumptions, that may result from their use. Thus, what possible revision of the GDPR is needed should be considered as it transmits to the primary research question, which is related to how profiling and algorithms are being used for automated decision-making, and how the national law or GDPR should be used to respond to those threats
Keywords: Data protection; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law